SEBARAN DAN KARAKTER MORFOLOGI Endiandra (LAURACEAE) DARI SUMATRA, KOLEKSI HERBARIUM BOGORIENSE, PUSAT PENELITIAN BIOLOGI-LIPI - Nalar Mutiara Esa; J Jumari; M Murningsih; Deby Arifiani (Departemen Biologi, Fakultas Sains dan Matematika Undip, 2016)
Herbarium are authentic evidence in the form of plants that serve as a reference of identification to identify plant species. Endiandra is one of genus of family Lauraceae and widely used, however, the name Endiandra still not very well known. Knowledge of the distribution and morphological characters Endiandra in Sumatra necessary to complete the information Endiandra in Malesia region. Research using herbarium specimens Endiandra of Sumatra in the Herbarium Bogoriense with morphological approach and use the information on the specimen label to graph the distribution of heights and distribution maps using ArcGIS software. The characters are important in distinguishing the types Endiandra in Sumatra ie hair; presence or absence of, a lot or a little, the number of lateral veins of leaves and surface texture of the leaves and stems. Endiandra scattered in every province of Sumatra island in the lowlands to highlands 3-1100 meters above sea level from 1200 to 2000 meters above sea level.Keywords: Endiandra, morphology, distribution, Sumatra.